Design, Synthesis, and Biological Evaluation of [1,2,4]triazolo[4,3-a] Pyrazine Derivatives as Novel Dual c-Met/VEGFR-2 Inhibitors - Liu, Xiaobo; Li, Yuzhen; Zhang, Qian; Pan, Qingshan; Zheng, Pengwu; Dai, Xinyang; Bai, Zhaoshi; Zhu, Wufu (Frontiers in Chemistry, 2022)
In this study, we designed and synthesized a series of novel [1,2,4]triazolo [4,3-a]pyrazine derivatives, and evaluated them for their inhibitory activities toward c-Met/VEGFR-2 kinases and antiproliferative activities against tested three cell lines in vitro. Most of the compounds showed satisfactory activity compared with lead compound foretinib. Among them, the most promising compound 17l exhibited excellent antiproliferative activities against A549, MCF-7, and Hela cancer cell lines with IC50 values of 0.98 ± 0.08, 1.05 ± 0.17, and 1.28 ± 0.25 µM, respectively, as well as excellent kinase inhibitory activities (c-Met IC50 = 26.00 nM and VEGFR-2 IC50 = 2.6 µM). Moreover, compound 17l inhibited the growth of A549 cells in G0/G1 phase in a dose-dependent manner, and induced the late apoptosis of A549 cells. Its intervention on intracellular c-Met signaling of A549 was verified by the result of Western blot. Fluorescence quantitative PCR showed that compound 17l inhibited the growth of A549 cells by inhibiting the expression of c-Met and VEGFR-2, and its hemolytic toxicity was low. Molecular docking and molecular dynamics simulation indicated that compound 17l could bind to c-Met and VEGFR-2 protein, which was similar to that of foretinib.